2021
DOI: 10.1186/s12906-020-03199-6
|View full text |Cite
|
Sign up to set email alerts
|

A randomized placebo-controlled phase I clinical trial to evaluate the immunomodulatory activities of Atractylodes lancea (Thunb) DC. in healthy Thai subjects

Abstract: Background Atractylodes lancea (Thunb) DC. (AL) and bioactive compounds β-eudesmol and atractylodin have been demonstrated in the in vitro and in vivo studies for their potential clinical use in cholangiocarcinoma. The study was a randomized, double-blinded, placebo-controlled phase I clinical trial to evaluate the immunomodulatory effect of AL in human subjects. Methods The modulatory effects of AL and β-eudesmol and atractylodin on TNFα and IL6 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 58 publications
3
26
0
Order By: Relevance
“…DC. extract was linked with suppression of the production of TNF- α and IL6 cytokines, which are involved in the pathogenesis and severity of CCA 137 . A phase II dose-finding study is underway to confirm efficacy, tolerability, and immunomodulatory activity of A. lancea (Thunb.)…”
Section: Resultsmentioning
confidence: 99%
“…DC. extract was linked with suppression of the production of TNF- α and IL6 cytokines, which are involved in the pathogenesis and severity of CCA 137 . A phase II dose-finding study is underway to confirm efficacy, tolerability, and immunomodulatory activity of A. lancea (Thunb.)…”
Section: Resultsmentioning
confidence: 99%
“…In addition, organic acid component, as the main active ingredient of pugongying, can improve acute tracheobronchitis by downregulating the protein expression levels of TNF-α and IL-6 (Yang et al, 2016). The main chemical constituents of Fuping, the flavones apigenin and luteolin, can suppress inflammatory responses by mediating neutrophil apoptosis (Lucas et al, 2013); In addition, Cangshu, Zhizi, and Huangqi have also been confirmed to have anti-inflammatory and anti-oxidant effects (Xiao et al, 2017;Kulma et al, 2021;Li et al, 2022). Combined with the aforementioned results, it may be suggested that PPQH plays an anti-SASR-COV-2 effect through its antiviral and anti-inflammatory cytokine storm functions; however, further research is still needed.…”
Section: Discussionmentioning
confidence: 99%
“…Formulated AL and ATD are potential candidates and are currently under research and development for cholangiocarcinoma treatment [8,16,29]. Phase I clinical trial of AL showed promising safety and pharmacokinetic profiles [15], as well as immunomodulatory activity in healthy Thai subjects [30]. Phase II dose-finding study is currently in progress to find the most effective dose in patients with advanced stage cholangiocarcinoma.…”
Section: Plos Onementioning
confidence: 99%